The relationship between self-control and internet gaming disorder and problematic social networking site use: the mediation effects of internet use motives - Zhou, Ruoyu; Morita, Nobuaki; Zhu, Chunmu; Ogai, Yasukazu; Saito, Tamaki; Yang, Wenjie; Ogawa, Mitsue; Zhang, Hong (Frontiers in Psychiatry, 2024)
This study analysed the relationships between problematic social networking site use (PSNSU), Internet Gaming Disorder (IGD), motives for internet use, and self-control among university students in China and Japan. the The purpose of this study was to analyse the indirect effects between self-control and different types of internet addiction (IGD and PSNSU) via motives for internet use among male and Female female users. The sample consisted of 697 university students (465 female; 397 Chinese). Path analysis was conducted on male and Female female users to examine the relationships between the study variables. The findings revealed that the capacity for self-control exerted significant indirect effects on IGD through the motives of enhancement (β = 0.096**, p = 0.005), Social (β = -0.090**, p = 0.007), and conformity (β = -0.117**, p = 0.001). However, these indirect effects were only observed in the male group. Furthermore, the capacity for self-control also exhibited indirect effects on PSNSU through motives of enhancement, social, coping, and conformity. Motives for internet use had a greater impact on PSNSU compared to IGD. Gender differences in some mediating effects (enhancement, social, coping) were identified. These findings contribute to a better understanding of the extent to which motivations for internet use influence different types of problematic internet use.